PERAN PENGADILAN PAJAK DALAM MENYELESAIKAN SENGKETA PAJAK MELALUI MEDIA ELEKTRONIK BERDASARKAN PERATURAN PEMERINTAH REPUBLIK INDONESIA NOMOR 80 TAHUN 2019 - Harsojono Sukmana; Rizky Karo Karo (LEX OMNIBUS : Jurnal Hukum Tata Negara dan Administrasi Negara, 2025)
Government Regulation Number 80 of 2019 concerning Tax Administration has brought a breath of fresh air in tax reform in Indonesia, especially in terms of resolving tax disputes. One of the significant innovations introduced is the use of information technology, where the Tax Court is increasingly playing an active role in resolving tax disputes through electronic media. Although the use of electronic media in resolving tax disputes has many benefits, such as time and cost efficiency, as well as increased accessibility, there are several problems that need to be considered, namely laws and regulations, even though there is Government Regulation Number 80 of 2019, more detailed implementing regulations are still needed to regulate various technical aspects of the implementation of hearings electronically. The method used as a reference by the researcher is the normative approach. The normative approach is an approach that involves the analysis of theories, concepts, legal principles, and laws and regulations (State Approach) contained in the main legal materials related to this research. In resolving disputes in trade through electronic systems in accordance with the role of the Tax Court in resolving tax disputes through electronic media, it is increasingly strategic in order to realize a fair, effective, and efficient tax system. With the support of adequate laws and regulations and joint efforts from all stakeholders, it is hoped that the resolution of tax disputes in Indonesia can run better.